ANALISIS BAHASA MANTRA PENGOBATAN SAKIT MATA PADA USIA 3-4 TAHUN DESA ENSAID PANJANG - Sudarto, Sudarto; Mulyadi, Yohanes Berkhmas (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
Indonesia is a diverse nation with a wide range of cultural traditions, one of which is oral literature in the form of mantras practiced by the Dayak Desa community in Ensaid Panjang. These mantras, recited by traditional healers (dukun), are believed to have the power to cure illnesses. The healing process is still carried out traditionally, utilizing natural plants from the environment. This study focuses on a specific healing mantra used to treat eye ailments in children aged 3 to 4 years. The main problem explored in this research is: What is the linguistic structure of the healing mantras used by the Dayak Desa community in Ensaid Panjang? The purpose of this study is to analyze the linguistic style, meaning, and contextual use of the mantra. A descriptive qualitative method was employed, using a structural semiotic approach. The respondent in this study was a traditional healer. Data were collected through direct observation, semi-structured interviews, and audio recordings. The findings show that the linguistic style used in the healing mantra includes repetition techniques such as alliteration, symploce, and chiasmus. The meaning of the words in the mantra expresses requests and supplications to the Creator, hoping that the healing ritual will proceed smoothly and produce favorable results.